Sixty Years (1957–2017) of Research on Toxoplasmosis in China—An Overview - Pan, Ming; Lyu, Congcong; Zhao, Junlong; Shen, Bang (Frontiers in Microbiology, 2017)
Toxoplasma gondii is a ubiquitous zoonotic pathogen belonging to apicomplexan parasites. Infection in humans and animals may cause abortion and other severe symptoms under certain circumstances, leading to great economical losses and public health problems. T. gondii was first discovered in China in 1955 and the corresponding work was published in 1957. Since then, a lot of work has been done on this parasite and the diseases it causes. This review summarizes the major progress made by Chinese scientists over the last 60 years, and gives our perspectives on what should be done in the near future. A wide variety of diagnostic approaches were designed, including the ones to detect T. gondii specific antibodies in host sera, and T. gondii specific antigens or DNA in tissue and environmental samples. Further work will be needed to translate some of the laboratory assays into reliable products for clinic uses. Epidemiological studies were extensively done in China and the sero-prevalence in humans increased over the years, but is still below the world average, likely due to the unique eating and cooking habits. Infection rates were shown to be fairly high in meat producing animals such as pigs, sheep and chickens, as well as in the definitive host cats. Numerous subunit vaccines in the form of recombinant proteins or DNA vaccines were developed, but none of them is satisfactory in the current form. Live attenuated parasites using genetically modified strains may be a better option for vaccine design. The strains isolated from China are dominated by the ToxoDB #9 genotype, but it likely contains multiple subtypes since different ToxoDB #9 strains exhibited phenotypic differences. Further studies are needed to understand the general biology, as well as the unique features of strains prevalent in China.